Pivotal temperature is not for everyone: Evidence for temperature-dependent sex determination in three gecko species - Straková, Barbora; Kubička, Lukáš; Červenka, Jan; Kratochvíl, Lukáš (Journal of experimental zoology. Part A, Ecological and integrative physiology, 2024)
The prevalence of environmental sex determination (ESD) in squamate reptiles is often overestimated in the literature. This is surprising because we have reliable data demonstrating ESD in only a few species. The documentation of ESD in three species of geckos presented here has significantly increased our knowledge, given that satisfactory evidence for ESD existed in only eight other gecko species. For the first time, we document the occurrence of ESD in the family Sphaerodactylidae. Our finding of unexpected variability in the shapes of reaction norms among geckos highlights that traditional descriptions using parameters such as pivotal temperature, that is, temperature producing a 50:50 sex ratio, are unsatisfactory. For example, the gecko Pachydactylus tigrinus lacks any pivotal temperature and its sex ratios are strongly female-biased across the entire range of viable temperatures. We argue for the effective capture of the relationship between temperature and sex ratio using specific nonlinear models rather than using classical simplistic descriptions and classifications of reaction norms.
Keywords: sex determination; reptiles; druhová specificita; Temperature; ještěři; teplota; procesy určující pohlaví; Female; zvířata; Sex Ratio; ženské pohlaví; Sex Determination Processes; Male; Species Specificity; Lizards; poměr pohlaví; Animals; mužské pohlaví; temperature